2022
DOI: 10.21203/rs.3.rs-1396514/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probabilistic analysis of water-sealed performance in underground oil storage considering spatial variability of hydraulic conductivity

Abstract: For underground water-sealed oil storage, the spatial variability of the surrounding rock has a significant impact on the water-sealed effect of a water curtain system. This study presents a methodology for the probabilistic analysis of water curtain performance in underground oil storage, considering the spatial variability of hydraulic conductivity of the surrounding rock based on field data. Anisotropic random fields representing the spatial variability of hydraulic conductivity were established through spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…When the COV of failure probability is less than a certain value, this probability is regarded as the failure probability of a slope. In this paper, the COV failure probability can be determined according to Equation (16). If the value is less than 0.3, it is judged as computational convergence.…”
Section: Failure Probability Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…When the COV of failure probability is less than a certain value, this probability is regarded as the failure probability of a slope. In this paper, the COV failure probability can be determined according to Equation (16). If the value is less than 0.3, it is judged as computational convergence.…”
Section: Failure Probability Calculationmentioning
confidence: 99%
“…Griffiths et al [15] demonstrated that ignoring the spatial variability of soil parameters could lead to underestimating slope stability. Generally, natural spatial variability can be described by random fields and probabilistic methods are often used to evaluate landslide reliability [16][17][18]. Li et al [19] by combining the random finite element method with the Monte Carlo Simulation (MCS), thereby improving computational efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation